Effective dispersion compensation of variable-linewidth fiber amplifier by single-multilayer dielectric grating. (11th May 2016) - Zheng, Ye; Yang, Yifeng; Wang, Jianhua; Hu, Man; Liu, Guangbo; Chen, Xiaolong; Liu, Kai; Zhao, Chun; Gong, Weichao; Bai, Gang; Bai, Yang; He, Bing; et al.
Abstract: We achieve effective dispersion compensation by employing a single-multilayer dielectric diffraction grating and a variable-linewidth fiber amplifier. Both theoretical and experimental studies on the diffracted beam quality have been performed. The experimental results show that when the linewidth reaches 0.41 nm the beam quality in the dispersive plane reduces dramatically from 5.4 for the first-time diffracted beam to 2.08 for the second-time diffracted beam. This dispersion compensation technology relaxes the requirement on the linewidth of the incident beam source, which is beneficial for high-brightness spectral beam combining.